Fancy Dancer and the seven drums - Roskelley, John (Reverie, 2023)
"A nine-year-old Nez Perce Fancy Shawl pow wow dancer, Beth Louie, is killed on the reservation by a hit-and-run drunk driver while walking home from the bus stop with her younger brother. Tire marks and boot tracks on the remote gravel road suggest to a Colville tribal member Ben Moses and his grandson, Alex, who find the two children, that the driver of a pick-up truck tampered with the scene and evidence, and hid the body. Tribal law enforcement and the FBI are stymied, but evidence points to a white cattle rancher from Omak as the prime suspect. In the prejudicial environment of the 1950s, will an all-white Spokane jury convict and send the killer to jail?" --Adapted from book jacket.